2019
DOI: 10.24985/kjss.2019.30.4.700
|View full text |Cite
|
Sign up to set email alerts
|

Verifying the worksheets for improving life skills and resilience of collegiate Taekwondo athletes

Abstract: Purpose The purpose of this study was to verify their effectiveness as we develop and apply worksheets for improving life skills and resilience of collegiate Taekwondo athletes. Methods The study went through three stages: developing, applying, and evaluating. In the developing stage, literature review, expert meeting, and pilot test (n=25) were conducted to develop the worksheets. In the applying stage, 37 athletes participated in life skills program using the worksheets. Data were collected by survey and in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
3
0
2
Order By: Relevance
“…While this study emphasizes the importance of the coach's role, multilevel analysis also reveals that individual athletes’ life skills development is a significant factor affecting transfer. The finding is consistent with those reported in a Korean study conducted on taekwondo athletes, 15 showing that athletes’ life skills development positively affects the transfer of life skills to other areas of life. In addition, recent study conducted on student-athletes in Korea 44 reported similar results, supporting the findings of this study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…While this study emphasizes the importance of the coach's role, multilevel analysis also reveals that individual athletes’ life skills development is a significant factor affecting transfer. The finding is consistent with those reported in a Korean study conducted on taekwondo athletes, 15 showing that athletes’ life skills development positively affects the transfer of life skills to other areas of life. In addition, recent study conducted on student-athletes in Korea 44 reported similar results, supporting the findings of this study.…”
Section: Discussionsupporting
confidence: 92%
“…7 Qualitative studies have been used to conceptualize sports-PYD and life skills, 4,8,9 such as measuring, developing, and evaluating student-athletes’ life skills, 10,11 the development and application of sports based life skill programs, 12,13 and statistical verification between variables that promote or result from life skills. 14,15 According to these studies, a key factor in determining the development and transfer of life skills of student-athletes is the role of significant others. These significant others are individuals who directly or indirectly interact with student-athletes, such as parents, coaches, teachers, and peers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…명시적 접근을 위해서는 리더의 '의도성'과 프로그램의 '체계성'이 수반되어야 한다 (Lim et al, 2019). 그러나 리더 혼자만의 노력으 로 의도성과 체계성을 보장하는 것은 어려운 일이다.…”
Section: 코칭 매뉴얼(적용)unclassified
“…관한 연구는 다방면으로 시도됐다 (Camiré & Santos, 2019). 예컨 대 스포츠 PYD와 라이프스킬을 개념화하기 위한 질적 연구 Hodge et al, 2013;Holt, 2016;Pierce et al, 2017), 학 생선수나 유소년의 라이프스킬을 측정하고 평가할 수 있는 도구 개 발 (Cronin & Allen, 2017;Weiss et al, 2014), 스포츠 라이프스킬 프로그램 개발 및 적용 (Hardcastle et al, 2015;Lim et al, 2019;Weiss, 2006), 라이프스킬을 촉진하거나 라이프스킬의 결과로 나 타나는 변인 간의 통계적 검증 (Cronin & Allen, 2018;Heo & Seo, 2019;Lim et al, 2020) 등 상당히 많은 연구 성과와 지식이 쌓였다.…”
unclassified